Lie Symmetry Analysis, Conservation Laws, Power Series Solutions, and Convergence Analysis of Time Fractional Generalized Drinfeld-Sokolov Systems - Gulsen, Selahattin; Yao, Shao-Wen; İnç, Mustafa (Mdpi, 2021)
In this work, we investigate invariance analysis, conservation laws, and exact power series solutions of time fractional generalized Drinfeld-Sokolov systems (GDSS) using Lie group analysis. Using Lie point symmetries and the Erdelyi-Kober (EK) fractional differential operator, the time fractional GDSS equation is reduced to a nonlinear ordinary differential equation (ODE) of fractional order. Moreover, we have constructed conservation laws for time fractional GDSS and obtained explicit power series solutions of the reduced nonlinear ODEs that converge. Lastly, some figures are presented for explicit solutions.
Keywords: conservation laws; Lie symmetry analysis; generalized Drinfeld– Sokolov systems; symmetry reduction; Erdelyi– Kober operators